Antibiotic Resistance and Its Molecular Mechanisms in Carbapenem-Nonsusceptible Klebsiella pneumoniae Isolated in Pediatric ICUs in Moscow - O. A. Kryzhanovskaya; A. V. Lazareva; N. M. Alyabieva; R. F. Tepaev; O. V. Karaseva; I. V. Chebotar; N. A. Mayanskiy (Антибиотики и Химиотерапия)
Klebsiella pneumoniae Is a significant pathogen associated with hospital infections. Its was isolated in intensive care units (ICU) at two pediatric hospitals in Moscow in 2012-2014 from 41% (387/935) of the patients. The rate of carbapenem-nonsusceptibility (Carba-NS) amounted to 25% for imipenem and 27% for meropenem. For further analyses, 67 isolates were selected, including 57 Carba-NS and 10 Carba-susceptible (Carba-S). Among the isolates, 100% was nonsusceptible to the III-IV generation cephalosporins, 50-84% was resistant to aminoglycosides. The rate of nonsusceptibility to ciprofloxacin and phosphomycin exceeded 90%. All the tested Carba-S K.pneumoniae isolates were susceptible to tigecycline, whereas 25% of the Carba-NS isolates was tigecycline-NS. The prevalence of the colistin-NS isolates was the same in Carba-S (20%) and Carba-NS (26%) bacteria. The blaCTX_M gene was carried by 100% of the Carba-S isolates, combining with the blaTEM gene in 60% of the isolates. In 89% of the Carba-NS isolates the OXA-48 carbapenemase was detected, which was combined with CTX-M and/or TEM in all but 1 isolate. Thus, over the last decade, the rate of Carba-NS among nosocomial K.pneumoniae increased and the OXA-48 carbapenemase was shown to be dominating in the mechanism of Carba-NS in the pediatric ICUs in Moscow.